ANALISA FAKTOR – FAKTOR YANG MEMENGARUHI FINANCIAL DISTRESS PADA PERUSAHAAN MANUFAKTUR DI INDONESIA - Syahrani, Yumni; Lasar, Hilary Flora A. T. (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
This study aims to obtain empirical evidence regarding the influence of leverage, operating capacity, profit margin, ownership concentration, board size, and audit committee as independent variables on financial distress as dependent variables. In this study, the research object was used for manufacturing companies listed on the Indonesia Stock Exchange (IDX) from the period of 2021 to 2023. Sampling in this study uses the purposive sampling method with samples, consisting of 121 manufacturing companies with 363 data that meet 4 specified criteria. This data processing uses SPSS 25. The results of this study show that leverage (DER), ownership concentration (OC), board size (BSIZE), and audit committee (AC) have no effect on financial distress while operating capacity (TATO) and profit margin (NPM) have an effect on financial distress.